“Menjadi Nutrition Champion di Media Sosial”: Peningkatan Kapasitas Kader Kesehatan dalam Upaya Pencegahan Anemia Kehamilan - Izzatul Arifah; Shania Salsabilla Alamsyah; Erin Tri Cahyanti (Universitas Muhammadiyah Surakarta, 2023)
The proportion of anemia is high among pregnant women in Indonesia making it a priority health problem, especially in various regions, including Central Java Province. Educational efforts to empower pregnant women are necessary. A nutrition Champion is necessary for the optimization of activities. Interviews show that the online pregnant women's class has been carried out but encountered obstacles such as the inactivity of participants and the busyness of each health worker. This service activity aims to increase the capacity of health cadres in becoming nutrition champions on social media for the prevention of anemia during pregnancy. The expected output target is that health cadres have media that are interesting and effective in educating in the form of electronic booklets. As well as an increase in knowledge and motivation of health cadres in becoming nutrition champions on social media to prevent anemia in pregnant women. The activity was carried out in June 2022 and attended by 30 health cadres offline in the Sangkrah Puskesmas work area (100% of the target). Electronic booklets have been disseminated and explained to all cadres. The evaluation results showed that the majority (80%) of cadre knowledge levels increased after training (p-value<0.001). The cadre of the Kratonan Health Center is then expected to become nutrition champions who help overcome the incidence of anemia in pregnant women in Surakarta. Periodic monitoring and education of health cadres need to be carried out to increase their role as nutrition champions for anemia prevention in the community.